2020
DOI: 10.1186/s13019-020-1059-8
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding complications after cardiac surgery, before anticoagulation start and then with argatroban or heparin in the early postoperative setting

Abstract: Objectives: After elective cardiac surgery a postoperative anticoagulation is obligatory. With critically ill patients the conventional anticoagulation standard heparin is sometimes impossible, e.g. based on HIT II. Then, argatroban is currently a possible alternative, however, due to its impaired metabolism in critically ill patients, anticoagulation effect is harder to anticipate, thus resulting in higher bleeding risk. Furthermore, to date no antidote is available. Hence, severe postoperative bleeding incid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…However, some moderate bleeding often occurs accompanying their applications in clinic. 10 , 11 The license of Rivaroxaban, a representative of direct oral anticoagulants (DOACs), brings more options to the anticoagulant market. Nevertheless, moderate or minor bleeding of rivaroxaban still puzzles doctors, especially for patients with high bleeding risk.…”
Section: Introductionmentioning
confidence: 99%
“…However, some moderate bleeding often occurs accompanying their applications in clinic. 10 , 11 The license of Rivaroxaban, a representative of direct oral anticoagulants (DOACs), brings more options to the anticoagulant market. Nevertheless, moderate or minor bleeding of rivaroxaban still puzzles doctors, especially for patients with high bleeding risk.…”
Section: Introductionmentioning
confidence: 99%
“…The relative risk of bleeding has been described for elective orthopedic and cardiovascular procedures with similar bleeding risks as tonsillectomy. 14,15 Unlike many cardiac or orthopedic patients, however, tonsillectomy patients are often young and very rarely require anticoagulation for any reason, which explains the lack of data on this topic.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with heparins such as LMWH or UFH, a retrospective study in critically ill patients diagnosed with HIT showed that argatroban used at doses less than 0.4 mg/kg/min was not associated with an increase in transfusion requirement and furthermore was associated with reduced overall treatment cost as compared to heparin [179]. Although risk factors for bleeding during argatroban are known [180], several retrospective studies have demonstrated that argatroban is well tolerated with bleeding rates comparable to those of heparin in critically ill patients suffering from various diseases other than HIT [181][182][183][184].…”
Section: Evidence For the Usefulness Of Argatroban In Sepsismentioning
confidence: 99%